PENERAPAN TEKNIK PENUGASAN PROYEK BERBASIS MASALAH (PROJECT BASED LEARNING) UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA PESERTA DIDIK KELAS IV SDN 123 BANGKO - Marta; Maulidnawati Jumrah, Abrina; Abdul Wahid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to improve the science learning outcomes of fourth-grade students at SDN 123 Bangko through the application of the Project Based Learning (PjBL) model. The subjects of this study were 15 students, consisting of 3 males and 12 females. The initial observation was conducted in March 2026, and the research action was carried out in April 2026. The research method used was Classroom Action Research (CAR) with a spiral model design consisting of two cycles. Data collection techniques included tests, observation, and documentation. The results showed that the application of the PjBL model significantly improved student learning outcomes. The classical learning completeness increased from 40% in the pre-cycle to 66.7% in the first cycle and reached 86.7% in the second cycle. Thus, the Project Based Learning model is effective in improving the science learning outcomes of fourth-grade students at SDN 123 Bangko.